Individualising coaching in Olympic and Paralympic worlds: an applied perspective - Simon, S.; Richards, P. (International Sport Coaching Journal, 2022)
This practical advance paper outlines the complexity of simultaneously coaching in Olympic and Paralympic disciplines of canoeing. The paper integrates applied experience from the Tokyo Games with a critical review of disability literature to explore the importance of the creation of shared mental models to inform the development of a performance vision in elite sport. The paper first addresses the design and development of complex performance visions, which underpins the delivery of such elite programmes. Secondly, and perhaps more importantly, the paper addresses the fundamental issue that Paralympic sport is not a microcosm of Olympic sport and that performance visions and coaching processes created in an able-bodied environment cannot be cut, copied, and pasted into a Paralympic setting. Offering applied insight from this unique dual perspective, the paper discusses the complexity of designing a well-structured performance vision. We propose that although such performance visions developed in Olympic and Paralympic contexts share some similarities, the design of shared mental models needs to be bespoke to the performance setting. The paper articulates the additional complexities of shared mental models deployed in a paracanoe setting and offers recommendations as to how we can better support the construction of performance visions in Paralympic sport.